2006
DOI: 10.1021/la0607757
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of Superhydrophobic Surfaces of n-Hexatriacontane

Abstract: Superhydrophobic surfaces of n-hexatriacontane were fabricated in a single-step process. The low surface energy of n-hexatriacontane together with the randomly distributed micro- and nanoscale roughness features guarantees very large contact angles and a small roll-off angle for water drops. The advantage of n-hexatriacontane superhydrophobic surfaces is their stability in the sense that they are impervious to chemical reactions and retain their wetting characteristics over a long period of time, as confirmed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
60
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(63 citation statements)
references
References 22 publications
3
60
0
Order By: Relevance
“…These values are comparable with the reported solid fraction values belonging to other disordered microstructures, for example, the results of Tavana et al [37] on thermal evaporated polymer (C36H74) surface or Wang et al [26] on branch-like structures of gold, resulting from galvanic exchange reaction. In the experiment of Tavana et al [37], the samples have suitable roughness for AFM studies, and the experimentally achieved solid fraction was reported to be ∼0.12. Our samples are highly rough and therefore inappropriate for AFM measurements to determine the f value experimentally.…”
Section: MM (B) 2475 Mm and (C) 396 Mm Respectively; And (D) A Magsupporting
confidence: 90%
“…These values are comparable with the reported solid fraction values belonging to other disordered microstructures, for example, the results of Tavana et al [37] on thermal evaporated polymer (C36H74) surface or Wang et al [26] on branch-like structures of gold, resulting from galvanic exchange reaction. In the experiment of Tavana et al [37], the samples have suitable roughness for AFM studies, and the experimentally achieved solid fraction was reported to be ∼0.12. Our samples are highly rough and therefore inappropriate for AFM measurements to determine the f value experimentally.…”
Section: MM (B) 2475 Mm and (C) 396 Mm Respectively; And (D) A Magsupporting
confidence: 90%
“…Others have used thermal evaporation of n-hexatriacontane (C 36 H 74 ) and shown that this also produces superhydrophobic surfaces. [24] Bhushan et al further developed this by combining thermal evaporation of n-hexatriacontane with micropatterned epoxy replicas as substrates so as to gain several orders of hierarchy, which increased the superhydrophobicity of the surface. [25] Here, we show that the nanoroughness of the thermally deposited n-hexatriacontane wax surface evolves in time via self assembly and this leads to a dramatic change in the wetting properties with a transition from hydrophobic to superhydrophobic characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…This small value suggests that water does not penetrate significantly into the spaces between the protrusions on the surface. [32] To test this, we also measured the sliding angle (SA) of the treated film. The water drops, with a volume of 10 lL, were observed roll off the superhydrophobic LDH film surface at an angle of ca.…”
mentioning
confidence: 99%